2021
DOI: 10.21203/rs.3.rs-793073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soluble Programmed Cell Death-1 Predicts Hepatocellular Carcinoma Development During Nucleoside Analogue Treatment

Abstract: Soluble immune checkpoint molecules are emerging novel mediators of immune regulation. However, it is unclear whether soluble immune checkpoint proteins affect the development of hepatocellular carcinoma (HCC) during nucleos(t)ide analogue (NA) treatment in patients with chronic hepatitis B virus infection. This study included 122 NA-naïve patients who received NA therapy. We assessed the associations of clinical factors, including soluble immune checkpoint proteins, with HCC development during NA treatment. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…36 Supporting this, several studies have shown that high serum sCTLA-4 levels predicted shorter RFS in patients with glioma 21 and colorectal cancer. 22 As for the hepatocellular carcinoma, Kozuca et al 37 tried to elucidate the associations of 16 soluble immune checkpoint proteins including sCTLA-4 with HCC development during nucleos(t)ide analogue (NA) treatment in 122 chronic hepatitis B (CHB) patients, However, there was no significant correlation between sCTLA-4 and HCC development. Nevertheless, when consider the tumor recurrence, we have now shown in this study serum sCTLA-4 level is associated with tumor recurrence in CHC-HCC patients with high sCTLA-4 levels had shorter RFS for early LR.…”
Section: Discussionmentioning
confidence: 99%
“…36 Supporting this, several studies have shown that high serum sCTLA-4 levels predicted shorter RFS in patients with glioma 21 and colorectal cancer. 22 As for the hepatocellular carcinoma, Kozuca et al 37 tried to elucidate the associations of 16 soluble immune checkpoint proteins including sCTLA-4 with HCC development during nucleos(t)ide analogue (NA) treatment in 122 chronic hepatitis B (CHB) patients, However, there was no significant correlation between sCTLA-4 and HCC development. Nevertheless, when consider the tumor recurrence, we have now shown in this study serum sCTLA-4 level is associated with tumor recurrence in CHC-HCC patients with high sCTLA-4 levels had shorter RFS for early LR.…”
Section: Discussionmentioning
confidence: 99%